¿Los Objetivos de Desarrollo Sostenible como solución a los problemas de la cooperación al desarrollo? Explorando cuestionamientos y propuestas a partir de las miradas de la sociedad civil valenciana - Sergio BELDA-MIQUEL; Carola CALABUIG-TORMO; Alejandra BONI (Revista Iberoamericana de Estudios de Desarrollo, 2020)
This study situats in the current debates on the adoption of Global Agenda 2030 and the Sustainable Development Goals and on the question if this can be considered and advancement or not. We focus in the specific case of the Spanish non-governmental development sector, in order to address if the Agenda can solve the problems felt by the stakeholders. From a more normative and positioned perspectives, we ask is the Agenda can contribute to address these problems from a more transformative perspective, that is, contributing to the repoliticization of development and aid. For this aim, we address the reflections and questionings that emerge from civil society in the case of Valencian development aid. These voices offer a challenging and a very interesting perspective from which we can unpack the Agenda and propose ways in which it can be adapted in order to advance towards a more transformative development aid.